Tatar Virtual Institute of Kayum Nasyri - Shaiakhmetova, Liliia; Shayakhmetova, Leysan; Khusnutdinov, Rasim; Sulkarnayeva, Assiya (Journal of History Culture and Art Research, 2017)
The article is devoted to the study of structure and activity of the network of centers of Tatar virtual Institute of Kayum Nasyri, created on the basis of Institute of Philology and Intercultural Communication after Leo Tolstoy of Kazan Federal University. The aim of the Institute of Kayum Nasyri is the desire to become a world brand in its field. In this context, the Institute relies on the experience of such world-known educational centers as the British Council, the Institute named after Goethe, Cervantes Institute, Confucius Institute and Institute by Yunus Emre. The Institute's activities are associated with the development of collaboration in the field of education, support, promotion and development of the Tatar language and culture in the regions of the Russian Federation, countries of near and far abroad. There are 7 educational-cultural centers in the Institute at this moment. Each center is supplied with educational, informative literature and fiction, as well as the video-conferencing system for training, conferences and events online. The Institute of Kayum Nasyri is named after the famous Tatar educator. As a fervent supporter of friendship between Russian and Tatar people, he was the first of the educators to acquaintance the Tatars with the Russian history and culture in their native language, translated into the Tatar language many textbooks on geography, physics, mathematics, etc. Kayum Nasyri at the time, made the Russian-Tatar dictionary, was the author of a textbook of Russian grammar for the Tatars, as well as of the significant works in the field of the Tatar linguistics.